A behavioural change package to prevent hand dermatitis in nurses working in the national health service (the SCIN trial): study protocol for a cluster randomised controlled trial. Issue 1 (December 2016) - Madan, Ira; Parsons, Vaughan; Cookson, Barry; English, John; Lavender, Tina; McCrone, Paul; Murphy, Caroline; Ntani, Georgia; Rushton, Lesley; Smedley, Julia; Williams, Hywel; Wright, Alison; et al.
Abstract Background Hand dermatitis can be a serious health problem in healthcare workers. While a range of skin care strategies and policy directives have been developed in recent years to minimise the risk, their effectiveness and cost-effectiveness remain unclear. Evidence now suggests that psychological theory can facilitate behaviour change with respect to improved hand care practices. Therefore, we will test the hypothesis that a behavioural change intervention to improve hand care, based on the Theory of Planned Behaviour and implementation intentions, coupled with provision of hand moisturisers, can produce a clinically useful reduction in the occurrence of hand dermatitis, when compared to standard care, among nurses working in the UK National Health Service (NHS) who are particularly at risk. Secondary aims will be to assess impacts on participants' beliefs and behaviour regarding hand care. In addition, we will assess the cost-effectiveness of the intervention in comparison with normal care. Methods/Design We will conduct a cluster randomised controlled trial at 35 NHS hospital trusts/health boards/universities, focussing on student nurses with a previous history of atopic disease or hand eczema and on nurses in intensive care units. Nurses at 'intervention-light' sites will be managed according to what would currently be regarded as best practice, with provision of an advice leaflet about optimal hand care to prevent hand dermatitis and encouragement to contact their occupational health (OH) department early if hand dermatitis occurs. Nurses at 'intervention-plus' sites will additionally receive a behavioural change programme (BCP) with on-going active reinforcement of its messages, and enhanced provision of moisturising cream. The impact of the interventions will be compared using information collected by questionnaires and through standardised photographs of the hands and wrists, collected at baseline and after 12 months follow-up. In addition, we will assemble relevant economic data for an analysis of costs and benefits, and collect information from various sources to evaluate processes. Statistical analysis will be by multi-level regression modelling to allow for clustering by site, and will compare the prevalence of outcome measures at follow-up after adjustment for values at baseline. The principal outcome measure will be the prevalence of visible hand dermatitis as assessed by the study dermatologists. In addition, several secondary outcome measures will be assessed. Discussion This trial will assess the clinical and cost effectiveness of an intervention to prevent hand dermatitis in nurses in the United Kigdom. Trial registration ISRCTN53303171 : date of registration, 21 June 2013.